Data Modeling of Impact of Green-Oriented Transportation Planning and Management Measures on the Economic Development of Small- and Medium-Sized Cities - Yuan Lu; Jinyan Shao; Yifeng Yao (Journal of Advanced Transportation)
With the rapid growth of urbanization and motorization in China in recent years, the demand for transportation in people’s work and daily lives has increased. In this context, a number of issues such as urban traffic congestion, energy consumption, and environmental pollution have become increasingly severe. As a result, the tremendous socioeconomic, resource, and environmental pressures have been placed on the development of urban transportation. Sustainable economic and social development requires green development as a precondition. The economical and efficient use of resources and the protection and improvement of the ecological environment are conducive to the formation of a new pattern of modernization for the harmonious development of man and nature. Transportation planning is an essential technical field for promoting the development of green and ecological cities, and it is one of the primary responsibilities of urban planning. The application of green ecological planning technology and the scientific and reasonable development of traffic planning and management measures can aid in reducing energy consumption and, thus, achieving the goal of environmental protection. In this field, green transportation is a mature green ecological planning technology. Green transportation development is not only a key solution to urban transportation problems, but also an essential means of achieving sustainable urban development, so it has become a hot topic in the field of transportation. As the ideal city of the postindustrial era, ecocity can serve as a model for the sustainable development of China’s small and medium-sized cities. After all, industrial development is an unsustainable path, so human society must embrace green development. The core of green development lies in shifting from an exclusive reliance on industrialization to the urban transformation into an ecological civilization. Given the current contradictions between economic growth and resource and environmental degradation, promoting green and environmentally conscious transportation planning with resource conservation in mind is a crucial means of resolving these contradictions. Government incentives and restrictions are essential for the development of green transportation. Therefore, it is crucial to study the impact of environmentally conscious transportation planning and management measures on the economic growth of small and medium-sized cities. This will provide relevant departments and stakeholders with guidance and a reference for formulating policies that will contribute to the harmonious development of China’s green transportation and economy.